2022
DOI: 10.3390/atmos13111742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MODIS Dark Target AOD Product with 3 and 10 km Resolution in Amazonia

Abstract: The techniques and analyses employed by remote sensing provide key information about atmospheric particle properties at regional and global scales. However, limitations in optical spectral models used to represent the different types of aerosols in the atmosphere and their effects (direct and indirect) are still one of the major causes of sources of uncertainties and substantial impacts in climate prediction. There are no studies yet in South America, especially in the Amazon Basin, that have evaluated the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(105 reference statements)
1
3
0
Order By: Relevance
“…These findings present a novel, yet unrealized threat to agricultural and natural ecosystems related to the impairment of plants' intrinsic capacity to accumulate adequate reserves prior to dormancy, following exposure to severe smoke. The observed impact may extend beyond temperate climatic zones, as the levels of smoke detected in this study were similar to those observed in Amazonia 23 . It is crucial to acknowledge that the reported impacts were only discernible through comparisons of NSC stores over several years across a large geographical area, utilizing hundreds of measurements, underlining the importance and necessity of long-term, largescale observations for understanding such ecological effects.…”
supporting
confidence: 86%
“…These findings present a novel, yet unrealized threat to agricultural and natural ecosystems related to the impairment of plants' intrinsic capacity to accumulate adequate reserves prior to dormancy, following exposure to severe smoke. The observed impact may extend beyond temperate climatic zones, as the levels of smoke detected in this study were similar to those observed in Amazonia 23 . It is crucial to acknowledge that the reported impacts were only discernible through comparisons of NSC stores over several years across a large geographical area, utilizing hundreds of measurements, underlining the importance and necessity of long-term, largescale observations for understanding such ecological effects.…”
supporting
confidence: 86%
“…Sites located in the Legal The time series of the AOD 550nm from the AERONET is depicted in Figure 4 for the sites in Alta Floresta, Ji Paraná, and Rio Branco. All sites exhibit a noticeable seasonality during the period spanning from 2006 to 2011, as expected, due to significant emissions resulting from fires that occur during the dry season [28,38]. Sites located in the Legal Amazon region manifest distinct variability characteristics throughout the year, highlighting both a wet season and a dry season.…”
Section: Statistical Methodologysupporting
confidence: 61%
“…During the dry season, there is a signi cant increase in average AOD in several regions of the southern Amazon (ROCHA; YAMASOE, 2013), especially in sites that are located in or close to the arc of deforestation, such as Alta Floresta and Ji-Paraná. This substantial increase is mainly attributed to regional emissions resulting from biomass burning, as well as the transport of aerosols from distant areas (Morais et al, 2022;Palácios et al, 2022). In addition, the central region of the Amazon is in uenced by the descending branch of the Hadley cell, which causes dry conditions, favoring the concentration of aerosols in the atmosphere (Rocha; Yamasoe, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, priority was given to using level 2.0 data from the AERONET Network, which represents the highest level of quality (Holben et al, 1998). These data are subject to a rigorous quality assurance protocol, including corrections for local factors, guaranteeing their reliability (Palácios et al, 2022). AOD was analyzed for measurements taken at 500 nm.…”
Section: Measured Datamentioning
confidence: 99%
See 1 more Smart Citation